Tendência temporal da morbimortalidade por tuberculose em indígenas e não indígenas, Mato Grosso, Amazônia Legal, 2001 – 2015 - Souza, Tony José de (2017)
Tuberculosis (TB) remains one of the main causes of morbidity and mortality in Brazil and in the world, especially in indigenous populations. The objective of this study was to analyze the temporal trend of tuberculosis morbidity and mortality in indigenous and non-indigenous populations in Mato Grosso from 2001 to 2015. Methodology: Observational, descriptive and retrospective epidemiological study of TB cases and deaths; And ecological study, of the temporal series type, of the incidence and mortality rates registered in the general population and the indigenous / non-indigenous race / color group. Both were based on secondary data from the demographic censuses of 2000 and 2010, and from the SINAN and Mortality Information System (SIM) of the Epidemiological Surveillance Coordination of the State Health Secretariat of Mato Grosso. The population of the descriptive study were all cases and deaths of TB, and of the ecological study the incidence rates and mortality in indigenous and non-indigenous, 2001- 2015. The data were organized in a database spreadsheet and used the application software SPSS for Windows 20.0 (Statistical Package for the Social Sciences) and Minitab 17.0 for statistical analysis. The analysis was performed in four stages: 1) characterization of the profile of cases and deaths, 2) comparison of cases and deaths in indigenous and nonindigenous, using the statistical method of comparison of two proportions, 3) estimation of incidence rates and mortality Per TB per 100,000 inhabitants in the general population and indigenous and non-indigenous race / color, based on the calculation method proposed by the Ministry of Health, 4) construction of the temporal distribution and analysis of the trend of tuberculosis incidence and mortality in indigenous and non-indigenous populations , using the Holt-Winters (HW) statistical model. Results: From 2001 to 2015, 21,840 cases of tuberculosis and 1214 deaths per TB in TM were reported. There was a predominance of cases in non-indigenous males, with 20 to 39 years of schooling, with low schooling and residents in urban areas, however, there was also a high occurrence in indigenous women and children under 9 years of age. The pulmonary clinical form was the most frequent in natives and supervised treatment was performed in (92.61%) of the cases in indigenous and (72.04%) of non-indigenous cases. Chest x-ray was the method used to diagnose TB in (90.50%) cases in indigenous and (76.36%) cases in non-indigenous patients. In relation to the deaths, there was a higher frequency in non-indigenous populations; however, there was still a high mortality among indigenous people over 60 years of age. The gross incidence rate in TM in the year 2015 was 37.63/100.000 and mortality 2.10/100.000. In indigenous populations, the observed incidence was 448.70/ 100.000 and the mortality rate was 19.01/100.00 inhabitants. When we proceeded with the temporal trend of TB morbidity and mortality according to race / color, there was an increasing trend of incidence among indigenous people over the last years (2011-2015) when compared to non-indigenous and general population. Conclusions: The findings of this study reveal the social disparities in the occurrence of TB and reinforce the need for effective public policies in the fight against TB, especially in the indigenous population of Mato Grosso.